OBESITAS DAN KOMPLIKASI PADA SISTEM RESPIRASI : KAJIAN LITERATUR - Diniah, Andini Hikmatu; Mardhotillah, Hanifah; Maulidiyah, Irma (Journal Medical Kuningan, 2025)
Obesity is one of the problems of nutritional status changes that often occur in society both in developed and developing countries. Changes in lifestyle and low physical activity result in the movement of non-communicable diseases and not only disrupt the body’s metabolic system but also disrupt the respiratory system. Respiratory system disorders due to obesity are often not realized by sufferers, so this literature review will examine the development of diseases related to the respiratory system caused by obesity. Some disease due to obesity that disrupt the respiratory system are asthma, OHS, OSA, and COPD where all of these conditions are identical to the narrowing of the respiratory tract and muscle weakness in the respiratory area. Lifestyle management such as diet modification, increasing physical activity are strategies that can be carried out in obesity management and lung health control which requires cooperation between the government and public health stakeholders.